Partisipasi Mahasiswa KKNT MBKM Sekolah Tinggi Ilmu Ekonomi (STIE) Bima Memeriahkan 17 Agustus 2022 - MUNIARTY, PUJI; Wulandari, Wulandari; Taufik, Taufik (Dharma: Jurnal Pengabdian Masyarakat, 2023)
Mentoring activities through community service at the KKN location took advantage of the 17 August moment as a form of participation in caring for the surrounding environment. The main goal is to build togetherness with the community at the KKN location. To carry out this service activity, the stages carried out are: preliminary study, discussion, activity reporting, and evaluation. The presence of students enlivened the competition by recruiting children who were assisted by the Koran as well as school children to actively enliven the commemoration of August 17, 1945 in Kendo Village. In addition, students are active in approaching the Kendo community regarding community activities to welcome August 17, 1945 in Kendo Village and dig up information on local wisdom that is usually done by the community. The August 17 activity became an incidental agenda for the STIE Bima KKNT MBKM work program because it was not stated in the main work program and daily work program. However, considering that KKN activities are a form of community service, it is deemed necessary to participate actively in these activities.